Does a Speaking Task Affect Second Language Comprehensibility?. Issue 1 (March 2015) - Crowther, Dustin; Trofimovich, Pavel; Isaacs, Talia; Saito, Kazuya
<x xml:space="preserve">Abstract</x> The current study investigated task effects on listener perception of second language (L2) comprehensibility (ease of understanding). Sixty university‐level adult speakers of English from 4 first language (L1) backgrounds (Chinese, Romance, Hindi, Farsi), with 15 speakers per group, were recorded performing 2 tasks (IELTS long‐turn speaking task and TOEFL iBT integrated listening/reading and speaking task). The speakers' audio recordings were evaluated using continuous sliding scales by 10 native English listeners for comprehensibility as well as for 10 linguistic variables drawn from the domains of pronunciation, fluency, lexis, grammar, and discourse. In the IELTS task, comprehensibility was associated solely with pronunciation and fluency categories (specifically, segmentals, word stress, rhythm, and speech rate), with the Farsi group being the only exception. However, in the cognitively more demanding TOEFL iBT integrated task, in addition to pronunciation and fluency variables, comprehensibility was also linked to several categories at the level of grammar, lexicon, and discourse for all groups. In both tasks, the relative strength of obtained associations also varied as a function of the speakers' L1. Results overall suggest that both task and speakers' L1 play important roles in determining ease of understanding for the listener, with implications for pronunciation teaching in mixed L1 classrooms and for operationalizing the construct of comprehensibility in assessments.